Post-pandemic intercultural development trends among American undergraduate students - Bailey, Taylor W.; Tanoos, James J. (Journal of International Students, 2025)
Shifts in attitudes toward tourism management have permeated the literature on consumer behavior since the COVID-19 pandemic. Marketing strategies have targeted young people because, in an increasingly digital social world, global travel is especially appealing to this demographic, which feels a sense of isolation exacerbated by the pandemic. Postpandemic studies indicate that intercultural awareness and experiences are particularly sought after by American youth, who are comparatively isolated geographically from the rest of the world. This isolation has led to a longstanding deficit in global intercultural knowledge, as typified by high failure rates among American expatriates employed abroad. This phenomenon has prompted American institutions of higher education to create short-term study abroads to immerse students in global experiences proactively. These have been increasingly offered since the pandemic.